The Empowering Forest Communities through the Application of the Sonokeling Tree Barcoding System as an Effort for Forestry Social Disaster Management in Wan Abdul Rahman Forest Park, Lampung Province - Octaviani, Eti Artiningsih; Hasibuan, Mhd Muhajir; maulana, sena; sari, nurika arum; Murda, Rio Ardiansyah (TeknoKreatif: Jurnal Pengabdian kepada Masyarakat, 2023)
Abstract Community Service entitled "Empowering Forest Communities through the Application of the Sonokeling Tree Barcoding System as an Effort for Forestry Social Disaster Management in Wan Abdul Rahman Forest Park, Lampung Province" is motivated by the condition of the Tahura Wan Abdul Rahman area which is vulnerable to illegal logging, especially the Sonokeling (Dalbergia latifolia). Illegal logging is one of the social disasters of forestry and threatens the sustainability of forests and the various resources in them. This is also faced with the limited personnel of related institutions in dealing with social disasters. Therefore, the PkM team consisting of ITERA lecturers from the Forestry Engineering Study Program assisted in gathering information regarding the potential of sonokeling stands in Tahura WAR and developing a barcoding system (QR Code) that would facilitate monitoring and securing rosewood stands from the threat of illegal logging. The barcoding system application is also expected to be able to support the Tahura WAR foster tree program which will be initiated later to increase community empowerment in maintaining forest sustainability. Keywords: foster tree, WAR Forest Park, QR Code